Strategi Tuturan Presiden Macron dalam Konferensi Choose Europe for Science: Analisis Pragmatik: Tindakan dan Fungsi Lokutif dalam Pidato Presiden Macron pada KTT “Choose Europe for Science”: Kerangka Kerja Searle–Leech - Raditya Wilmar Ghivari; Yuliarti Mutiarsih; Iim Siti Karimah (Language Development Center, 2026)
Background: This study discusses how Macron uses language strategically in his “Choose Europe for Science” speech to promote academic freedom and encourage international scientific collaboration. Beyond its political dimension, the speech reflects a deliberate effort to frame science as a shared European responsibility, conveyed through carefully selected pragmatic theories. Purpose: The purpose of this study is to examine the categories of illocutionary acts and the illocutionary functions employed in Macron’s speech by applying a pragmatic perspective. Method: This research employs a descriptive qualitative approach. A total of 189 utterances were selected from the official transcript of the “Choose Europe for Science” summit. The analysis is based on Searle’s (1979) illocutionary act categories and Leech’s (1983) illocutionary functions. Data analysis was conducted through systematc coding procedures to reveal the pragmatic patterns which present in his speech.. Results and Discussion: The results show that representative acts are the most frequently used category (57.14%), followed by directive, commissive, expressive, and declarative acts. This pattern suggests that the speech relies strongly on factual statements while also seeking to mobilize and guide its audience. In terms of illocutionary functions, collaborative functions dominate (77.25%), accompanied by convivial, competitive, and conflictive functions. These findings indicate a combination of informative, persuasive, polite, and critical communicative strategies. Overall, the analysis demonstrates how pragmatic choices are used to establish scientific credibility, influence audience perception, and subtly criticize policies viewed as barriers to scientific progress. By focusing on a scientific political forum that has rarely been examined in previous studies of Macron’s rhetoric, this research contributes to filling an existing gap in the literature. Conclusions and Implications: The study concludes that Macron’s speech is pragmatically organized to promote scientific diplomacy through the strategic use of illocutionary acts. These findings highlight the potential for further research using multimodal or corpus-based methods to deepen the understanding of political pragmatics, particularly within post-pandemic scientific discourse.